2011
DOI: 10.1167/iovs.10-6366
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Characteristics of Central Retinal Artery and Vein Endothelium in the Normal Human Optic Nerve Head

Abstract: Arterial-like appearance of venous endothelium in the posterior lamina cribrosa, where pressure gradient forces are predicted to be greatest and CRV luminal diameter is known to be narrowest, implicates this as a site of altered hemodynamic stress. Heterogeneity of venous endothelium may have relevance for understanding ocular vascular diseases such as central retinal vein occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Recent studies have identified location-specific phenotypic differences of endothelium at the level of venous microvasculature. Studies of endothelial cell morphology in the central and branch retinal veins in human donor eyes 33,34 have found site-specific changes at these locations known to be vulnerable to venous occlusive diseases. A concept of a local venous constriction induced by vasoconstrictive molecules diffusing from neighboring diseased arteries and/or from other neighboring (hypoxic) tissues has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified location-specific phenotypic differences of endothelium at the level of venous microvasculature. Studies of endothelial cell morphology in the central and branch retinal veins in human donor eyes 33,34 have found site-specific changes at these locations known to be vulnerable to venous occlusive diseases. A concept of a local venous constriction induced by vasoconstrictive molecules diffusing from neighboring diseased arteries and/or from other neighboring (hypoxic) tissues has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-luminal microperfusion and staining technique has been established in our laboratory and used for study on retinal and choroidal vasculature (Adam et al, 1997;Chan et al, 2013;Kang et al, 2011Kang et al, , 2013Tan et al, 2012;Tan et al, 2013;Yu et al, 2014Yu et al, , 2010aYu et al, , 2010bYu et al, , 2013Yu et al, , 2012. Advantages of this technique include full perfusion fixation of the tissues and intact vasculature and endothelium in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most of the vascular remodelling studies focus on large arteries and arterioles but only a few have investigated remodelling in microvessels, a site that allows macromolecules to escape, resulting in tissue oedema and organ dysfunction (Yuan and He, 2012). We have previously reported vascular modelling in the specific sites of the retinal vein, arteriovenous crossing and laminar cribrosa region where risk sites for retinal vein occlusion are present (Kang et al, 2011(Kang et al, , 2013Yu et al, 2014;Yu et al, 2012). Identifying the structural and functional changes in iris microvascular endothelial cells and their impact on microvessel permeability will be crucial for a better understanding of the pathogenesis of related vascular diseases and thereby benefit the development of targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell length (ECL) measurements were taken as the longitudinal distance from the upstream pole to the downstream pole. Nuclei position was defined as the distance from the nuclear edge to the cell apex in the downstream direction of blood flow (hereafter denoted as variable e) (Kang et al, 2011). The ratio of e to ECL was considered as normalized nuclei position regardless of endothelial cellular size.…”
Section: Image Analysismentioning
confidence: 99%